DIVERSITY OF SEA CUCUMBER (ECHINODERMATA: HOLOTHUROIDEA) IN SABU RAIJUA WATERS, SABU ISLAND, EAST NUSA TENGGARA - Marcelien Dj Ratoe Oedjoe; Crisca B. Eoh (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2015)
Sea cucumber has an ecological function as an organic decomposer in sediment and nutrient producer within a food chain. In addition, sea cucumber has also economic values as fisheries and trade commodities. The pupose of this research was to investigate diversity of sea cucumber in the Sabu Raijua waters, East Nusa Tenggara Province. Samples were collected from Sabu Raijua waters in July -August 2014 using transect quadrant of 1x1 m2 during the lowest low tide in daytime at 13:00-16:00 and nighttime at 18.00-22.00 Central Standar Local Time. Data analyses on the sea cucumber were based on composition, density, distribution, and eating habits. The results showed that there were 8 species that can be classified into 3 families i.e., the Holothuridae (Holothuria nobilis, Holothuria scabra, Holothuria atra, Holothuria edulis, Holothuria impatiens, and Holothuria leucospilato); the Actinopyga (Actinopyga lecanora); and the Bohadshia (Bohadschia argus). The density of Holothuria nobilis was 5.651 individual/m2, Holothuria atra of 4.409 individual/m2, Holothuria scabra of 3.294 individual/m2; Holothuria edulis of 3.102 individual/m2; Bahaschia argus of 2.102 individual/m2; Holothuria mexicana of 2.088 individual/m2; Holothuria impatiens of 2.044 individual/m2; and Actinopyga lecanora of 1.037 individual/m2. Of these sea cucumber species, 17.3% were distributed on sandy substrate and 82.7% on seagrass and coral subtsrates. All sea cucumber species have a posi-tive association with its environment indicating that the water quality was still in a good condition. Keywords: sea cucumber, association, diversity, composition, distribution